Shaky roads and trembling exports: Assessing the trade effects of domestic infrastructure using a natural experiment - Christian Volpe Martincus; Juan Blyde (Inter-American Development Bank (IDB), 2012)
Our knowledge of the trade effects of domestic infrastructure is very limited. The reason is twofold. First, data needed to examine these effects are not readily available. Second, identifying such effects requires properly addressing potential endogeneity problems affecting the relationship between internal infrastructure and trade. In this paper, we overcome these limitations by combining firm-level data with detailed geo-referenced information on Chile and by exploiting the earthquake that took place in this country in 2010 as an exogenous source of variation in available infrastructure and thereby in transport costs. We find that diminished transportation infrastructure had a significant negative impact on firms' exports.
hdl:11319/4650
Keywords: F10; F14; D22; H54; R40; C25; 330; Firms; Transport Infrastructure; Exports; Chile